(untitled) (Stato, Chiese e pluralismo confessionale, 2024)
Ora et labora in the times of pluralism. The Philosophy of the American Supreme Court on School Prayer ABSTRACT: The paper investigates the philosophical elements implied in the decisions of the US Supreme Court on school prayers. To this end, the article first reconstructs the landmark opinions on the topic in the early Sixties, the consolidation of a strong separation between State and Church in the last three decades of the XX century and, finally, the affirmation of a new paradigm, more concessive towards school prayers, in the recent Kennedy decision of 2022. This historical overview outlines the legal framework of the issue to advance a twofold philosophical point. First, US Supreme Court jurisprudence on school prayers is characterized by the tension between two approaches to religion in pluralistic societies: neutrality on the one hand and toleration on the other. Second, school prayer cases evoke the clash between legislative and judicial power theorized in the literature as the “counter-majoritarian difficulty”. On this aspect as well, the two philosophical perspectives identified above can be further characterized by observing neutrality’s dynamic-static view on the issue opposing the toleration’s static-dynamic one. SOMMARIO: 1. Introduzione - 2. Le sentenze apripista degli anni Sessanta - 3. Il consolidamento del principio di neutralità - 4. La svolta Kennedy del 2022 - 5. La preghiera nelle scuole fra neutralità e tolleranza - 6. La preghiera nelle scuole e la difficoltà contro-maggioritaria - 7. Conclusione.